Worth the risk? An evaluation of alternative finance mechanisms for residential retrofit. (May 2019) - Brown, Donal; Sorrell, Steve; Kivimaa, Paula
Abstract: Improving energy efficiency, de-carbonising heating and cooling, and increasing renewable microgeneration in existing residential buildings, is crucial for meeting social and climate policy objectives. This paper explores the challenges of financing this 'retrofit' activity. First, it develops a typology of finance mechanisms for residential retrofit highlighting their key design features, including: the source of capital ; the financial instrument(s) ; the project performance requirements; the point of sale ; the nature of the security and underwriting the repayment channel and customer journey . Combining information from interviews and documentary sources, the paper explores how these design features influence the success of the finance mechanisms in different contexts. First, it is shown that a low cost of capital for retrofit finance is critical to the economic viability of whole-house retrofits. Second, by funding non-energy measures such as general improvement works, finance mechanisms can enable broader sources of value that are more highly prized by households. Thirdly, mechanisms that reduce complexity by simplifying the customer journey are likely to achieve much higher levels of uptake. Most importantly we discuss how finance alone is unlikely to be a driver of demand for whole-house retrofit, and so instead should be viewed as a necessary component of a much broader retrofit strategy. Highlights: Energy efficiency finance is an important but under research area. 'Finance mechanisms' are necessary for the uptake of residential energy efficiency. We identify six key design features that differentiate key types of mechanism. The cost of capital, customer journey and funding for wider measures are important for success. Finance alone is unlikely to be a driver of demand for residential energy efficiency.